Immunologic targeting of CD30 eliminates tumourigenic human pluripotent stem cells, allowing safer clinical application of hiPSC-based cell therapy - Nagako Sougawa (Nature Portfolio, 2018)
Abstract Induced pluripotent stem cells (iPSCs) are promising candidate cells for cardiomyogenesis in the failing heart. However, teratoma/tumour formation originating from undifferentiated iPSCs contaminating the graft is a critical concern for clinical application. Here, we hypothesized that brentuximab vedotin, which targets CD30, induces apoptosis in tumourigenic cells, thus increasing the safety of iPSC therapy for heart failure. Flow cytometry analysis identified consistent expression of CD30 in undifferentiated human iPSCs. Addition of brentuximab vedotin in vitro for 72 h efficiently induced cell death in human iPSCs, associated with a significant increase in G2/M phase cells. Brentuximab vedotin significantly reduced Lin28 expression in cardiomyogenically differentiated human iPSCs. Transplantation of human iPSC-derived cardiomyocytes (CMs) without treatment into NOG mice consistently induced teratoma/tumour formation, with a substantial number of Ki-67–positive cells in the graft at 4 months post-transplant, whereas iPSC-derived CMs treated with brentuximab vedotin prior to the transplantation did not show teratoma/tumour formation, which was associated with absence of Ki-67–positive cells in the graft over the same period. These findings suggest that in vitro treatment with brentuximab vedotin, targeting the CD30-positive iPSC fraction, reduced tumourigenicity in human iPSC-derived CMs, potentially providing enhanced safety for iPSC-based cardiomyogenesis therapy in clinical scenarios.